Heats of Adsorption of Aliphatic Alcohols on α-AlO at 25–200°C. II. Variations with Chain Length - Pier Francesco Rossi; Paola Rossi (Adsorption Science & Technology, 1997)
The adsorption of the first five members of the aliphatic alcohol series on α-Al 2 O 3 has been studied at 25–200°C by means of a heat-flow Calvet microcalorimeter (moderately high temperature). At very low coverage and at 25°C, the values of the differential heats of adsorption of the different alcohols were very high (250–200 kJ/mol) and were apparently independent of the chain length. However, at average coverage, the chain length of the alcohol began to influence both the values and the trends in the differential heats of adsorption of the various alcohols on α-Al 2 O 3 . Finally, at high coverage, it was found that the incorporation of each additional –CH 2 –group in the homologous series led to a decrease in both the integral heat of adsorption and the amount of alcohol adsorbed according to the series MeOH > EtOH > 1-PrOH > 1-BuOH > 1-PeOH. Increasing the temperature led to an increasing dependence of the differential heat on the chain length of the alcohol. In addition, from measurements of the thermokinetic parameters for the heat emission peaks for the adsorbed alcohols, it has been deduced that all five aliphatic alcohols studied adsorb on to an α-Al 2 O 3 surface in an open-chain perpendicular fashion.